The Global Research Trends and Hotspots on Developmental Dysplasia of the Hip: A Bibliometric and Visualized Study - Wu, Haiyang; Wang, Yulin; Tong, Linjian; Yan, Hua; Sun, Zhiming (Frontiers in Surgery, 2021)
Background: Developmental dysplasia of the hip (DDH) is a common musculoskeletal disorder in newborns and also one of the most common cause of hip arthritis in adult females. Many topics concerning DDH still remain controversial and the global research trend in this field has not been well studied yet. The aim of the present study was to illustrate the overall knowledge structure, development trends, and research hotspots of DDH. Methods: The publications related to DDH from 1998 to 2020 were identified from the Web of Science Core Collection. Three bibliometric tools were used to conduct visualization and knowledge maps. Annual trends of publications, contributions of countries, institutions, authors, funding agencies and journals, clustering of keywords were analyzed. Results: A total of 2691 publications were included. The annual number of DDH publications showed an increasing trend worldwide. The United States has made the greatest contribution, with the largest number of publications, and the highest H-index. The most prolific institutions were Shanghai Jiao Tong University, Children’s Hospital of Philadelphia, and Shriners Hospital for Children. Professors Tönnis D, Harris WH, Crowe JF, Graf R, and Salter RB have made great achievements to this field. However, Collaboration between international institutions or researchers was relatively low and mainly conducted in European and American countries. All the keywords could be divided into five clusters: hip osteoarthritis study, hip replacement study, hip ultrasound study, osteotomy surgery study, and etiology study. A trend of balanced and diversified development existed in these clusters. Keywords with the ongoing bursts, including clinical outcome, risk factor, femoroacetabular impingement, predictor, arthroscopy, morphology, and anteversion, may continue to be the research hotspots in the near future. Conclusions: There will be an increasing number of publications on the DDH research and the United States stay ahead in this field. International collaboration needs to be further strengthened. The information can provide helpful references for researchers to explore hot issues or target a specific field of DDH.